Pharmacotherapy of glaucoma in terms of evidence-based medicine - Fedorov, V. N.; Vdovichenko, V. P.; Korsakov, M. K.; Strakhov, V. V.; Popova, A. A.; Khokhlov, A. I.; Suleymanov, S. S. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2023)
Glaucoma is a disease associated with increased intraocular pressure (IOP). Of the pharmacological agents for treating glaucoma, there are drugs of the first (most effective and safe) and second-line treatment. First-line treatment includes prostaglandin analogs and beta-blockers. The currently used prostaglandin analogs (latanoprost, bimatoprost, tafluprost and travoprost) are PG F2α analogs that act through stimulation of FP receptors. They are distinguished by the optimal ratio of effectiveness and risk of side effects. They are convenient for the patient because for the therapeutic effect, it is enough to prescribe 1 time per day. As a result, it is rational to start the treatment of glaucoma with a drug in this group. In terms of pharmacoeconomics, the most affordable prostaglandin drug is latanoprost, which is generally as effective as other prostaglandin analogs. β-adrenergic blockers reduce the production of intraocular fluid, the formation of which is controlled by β1- and β2-adrenergic receptors. Therefore, non-selective β-blockers (timolol, levobunolol, metipranolol, and carteolol) have a pharmacodynamic advantage over selective β1-adrenergic antagonists (betaxolol). Conducted clinical studies of β-blockers have shown that given the cost, efficacy and safety, timolol was the most preferable treatment for glaucoma. In the presence of medical contraindications to the use of first-line drugs or to enhance their effectiveness, α2-agonists (apraclonidine and brimonidine), carbonic anhydrase inhibitors (usually local action: dorzolamide and brinzolamide), M-cholinomimetics (pilocarpine, carbachol and echothiopate), and also Rho-kinase inhibitors (ripasudil)